Implementasi Budidaya Teripang di Desa Madwaer, Maluku Tenggara - Pitjont Tomatala; Meyske Angel Rahantoknam (Universitas Mathla'ul Anwar Banten, 2017)
IMPLEMENTATION OF SEA CUCUMBER CULTIVATION IN MADWAER VILLAGE, SOUTHEAST MALUKU. Sea cucumbers or Teripang (Holothuria sp) is a fishery commodity that has economic value. Sea cucumbers are often caught and sold by a group of people in Madwaer village, Southeast Maluku regency. The value of perceived benefits motivates them (partners) to try to cultivate sea cucumbers by utilizing the coastal conditions in their village. Limitations of knowledge about the technique of making cucumber cultivation container, technology of sea cucumber rearing and management of sea cucumber business is a problem faced by partners. This activity aims to help partners solve the problems faced. The method used in this activity is elucidation, training and monitoring. From the results of the activity is known that partners have had the knowledge and skills so that they are able to make a good cultivation cucumber container, able to cultivate sea cucumbers and partners are able to do the management of sea cucumber business well.